Challenges in relating to mental health professionals: Perspectives of persons with severe mental illness. (29th May 2013) - Ådnøy Eriksen, Kristin; Arman, Maria; Davidson, Larry; Sundfør, Bengt; Karlsson, Bengt
Abstract A previous analysis showed that mental health service users experienced profound loneliness, struggled to relate to other people, and were careful in considering what to share with health‐care professionals. Being recognized by professionals in relationships may contribute to recovery processes characterized by 'connectedness', 'hope and optimism', 'identity', 'meaning', and 'empowerment'. This paper regards people as mainly seeking contact and meaning (relational perspective) and aims to describe service users' understanding of being in relationships with professionals, and how these relationships may limit or enhance recovery. Interpretative phenomenological analysis was used to analyze data from in‐depth interviews. Participants described three levels of connectedness with professionals: (i) being detached; (ii) being cautious; and (iii) being open and trusting. Level of connectedness seemed to be associated with opportunities for promoted recovery. Trusting relationships may strengthen identity, provide opportunities for meaning and hope, and contribute to opening new perspectives, and lessen significance of internal voices. Adopting a relational perspective may assist professionals in recognizing the service user as a person involved in making sense of life experiences and in the process of connecting to other people.